2020
DOI: 10.48550/arxiv.2001.06000
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterizing spin-one Kitaev quantum spin liquids

Ilia Khait,
P. Peter Stavropoulos,
Hae-Young Kee
et al.

Abstract: Material realizations of the bond-dependent Kitaev interactions with S=1/2 local moments have vitalized the research in quantum spin liquids. Recently, it has been proposed that higher-spin analogues of the Kitaev interactions may also occur in a number of materials with strong spin-orbit coupling. In contrast to the celebrated S=1/2 Kitaev model on the honeycomb lattice, the higherspin Kitaev models are not exactly solvable. Hence, the existence of quantum spin liquids in these systems remains an outstanding … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…For the spin-S Kitaev models, we have given analytical arguments why the residual entropy is S max /2, in agreement with previous numerical results [43]. When additional terms are added to higher spin Kitaev Hamiltonian [29], there is numerical evidence that there may still be a residual entropy, but it may not have a simple value as in the pure Kitaev case. Indeed, a double peaked structure in the heat capacity and a plateau-like feature in the entropy with varying values are being discussed as experimental signatures of Kitaev physics [35,38,40].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…For the spin-S Kitaev models, we have given analytical arguments why the residual entropy is S max /2, in agreement with previous numerical results [43]. When additional terms are added to higher spin Kitaev Hamiltonian [29], there is numerical evidence that there may still be a residual entropy, but it may not have a simple value as in the pure Kitaev case. Indeed, a double peaked structure in the heat capacity and a plateau-like feature in the entropy with varying values are being discussed as experimental signatures of Kitaev physics [35,38,40].…”
Section: Discussionsupporting
confidence: 87%
“…While much interest has justifiably focused on spin-1/2 Kitaev materials, it has been shown that Kitaev models with arbitrary spin retain many interesting properties [20][21][22][23][24][25][26][27][28][29]. For arbitrary spin, the system is a classical spin-liquid at intermediate temperatures, with only very short-range spin correlations and an extensive classical degeneracy.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic field effects on the S=1 Kitaev model have also been investigated. [26][27][28] The bond-dependent interactions have recently been adopted into TMT systems, because the nearest neighbour (n.n.) Heisenberg J, Kitaev K and Γ interactions * hykee@physics.utoronto.ca are allowed based on the symmetry of the lattice.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the spin-1/2 model, the higherspin Kitaev models are not exactly solvable. On the other hand, there exist numerical studies of the S = 1 Kitaev model supporting the existence of a quantum spin liquid ground state [32,[35][36][37][38][39][40]. In particular, an earlier study proposes the tensor network wavefunction for the S = 1 Kitaev quantum spin liquid [37].…”
mentioning
confidence: 99%